Infiltrating Foxp3+ Regulatory T Cells From Spontaneously Tolerant Kidney Allografts Demonstrate Donor‐Specific Tolerance. Issue 11 (18th September 2013) - Hu, M.; Wang, C.; Zhang, G. Y.; Saito, M.; Wang, Y. M.; Fernandez, M. A.; Wang, Y.; Wu, H.; Hawthorne, W. J.; Jones, C.; O'Connell, P. J.; Sparwasser, T.; et al.
Abstract: Foxp3 + regulatory T cells (Tregs) have an essential role in immune and allograft tolerance. However, in both kidney and liver transplantation in humans, FOXP3 + Tregs have been associated with clinical rejection. Therefore, the role and function of graft infiltrating Tregs have been of great interest. In the studies outlined, we demonstrated that Foxp3 + Tregs were expanded in tolerant kidney allografts and in draining lymph nodes in the DBA/2 (H‐2 d ) to C57BL/6 (H‐2 b ) mouse spontaneous kidney allograft tolerance model. Kidney allograft tolerance was abrogated after deletion of Foxp3 + Tregs in DEpletion of REGulatory T cells (DEREG) mice. Kidney allograft infiltrating Foxp3 + Tregs (K‐Tregs) expressed elevated levels of TGF‐β, IL‐10, interferon gamma (IFN‐γ), the transcriptional repressor B lymphocyte‐induced maturation protein‐1 (Blimp‐1) and chemokine receptor 3 (Cxcr3). These K‐Tregs had the capacity to transfer dominant tolerance and demonstrate donor alloantigen‐specific tolerance to skin allografts. This study demonstrated the crucial role, potency and specificity of graft infiltrating Foxp3 + Tregs in the maintenance of spontaneously induced kidney allograft tolerance. Abstract : The authors study regulatory T cells from tolerant kidney allografts and demonstrate that these cells exhibit potent and specific suppression.